Berlin, ville créative : enjeux socio-spatiaux d’une stratégie de développement urbain - Camille Boichot (Bulletin de l’Association de Géographes Français)
Since the early 2000’, Berlin, capital city of Germany, is knowing new “creative” urban policies. Inspired of the successful “creative city” model, local politicians are trying to put forward the cultural as well as the economic dynamism of a city that hardly comes out of the desindustrialisation economic crisis. How have these policies been developed in Berlin? What consequences do they have in terms of socio-spatial organisation of urban spaces?